Europe’s digital future: focus on key priorities - Ohnemus, Jörg; Bertschek, Irene (Mannheim, 2016)
"Customised products and services, flexible working arrangements, productivity growth, and increasing prosperity – these are just some of the advantages promised by a digitised and connected economy. Business managers and politicians are keen to reap the potential benefits of the digital transformation. Such a transformation of the economy, however, is a complex task which goes hand in hand with a significant number of challenges. Digital transformation brings about changes in production and innovation processes, in markets and working environments, and also has societal implications. In particular, there are widespread fears that the increased use of machines and robots for tasks previously completed by humans shall result in job losses. Actors at both European and national levels have launched numerous agendas, initiatives and directives in order to support the digital transformation. The Digital Agenda, part of the Europe 2020 Strategy consists of seven pillars (EU Commission, 2016a): i) Digital Single Market, ii) Interoperability & Standards, iii) Trust & Security, iv) Fast and ultra-fast Internet access, v) Research and innovation, vi) Enhancing digital literacy, skills and inclusion, vii) ICT-enabled benefits for EU society. These seven pillars comprise 132 actions ranging from simplifying Pan-European licensing for online works (action 1), to investing in High-Performance Computing (action 132)."